ATL. Issue 4 (1st July 2013) - Chen, Yu-Wen; Lin, Min-Fei; Chen, Yu-Chung; Hung, Ching-Hsia; Tzeng, Jann-Inn; Wang, Jhi-Joung
Abstract : Background: Exercise creates a variety of psychophysical effects, including altered pain perception. We investigated whether physical exercise reduces postincisional pain and cytokine and N -methyl-D-aspartate receptor 1 (NR1) expression in a rat model of skin/muscle incision and retraction (SMIR)–evoked pain. Methods: Male Sprague-Dawley rats were divided randomly into 4 groups: sham operated, SMIR-sedentary (SS), SMIR-exercise, and sham operated–exercise. On postoperative day 8, trained rats started to run on a treadmill 55 min/d with an intensity of 18 meter/minute (m/min), 5 days per week for 4 weeks. NR1, tumor necrosis factor α (TNF-α), and interleukin 6 (IL-6) expressions in the spinal cord as well as mechanical hypersensitivity following SMIR surgery were assessed for 6 to 35 days. Results: On postoperative day 6, SMIR-sedentary rats exhibited a marked hypersensitivity to von Frey stimuli. By contrast, SMIR-operated rats undergoing exercise demonstrated a quick recovery of mechanical hypersensitivity. The levels of TNF-α, IL-6, and NR1 in the spinal cord were significantly increased in SS rats when compared with sham-operated rats on postoperative days 6, 21, and 35 after SMIR surgery. After the 4-week exercise intervention, the SMIR-exercise group showed lower NR1, TNF-α, and IL-6 expression in the spinal cord than those in the SS group. Conclusions: These results suggest that exercise training decreases persistent postsurgical pain caused by SMIR surgery. There appears to be a protective effect, probably relating to the decrease of NR1, TNF-α, and IL-6 expression in the spinal cord of SMIR rats, after exercise intervention.